It’s a Doge’s Life: Examining Term Limits in Venetian Doges’ Life Tenure - Juan J. Merelo (Histories, 2023)
During most of the lifespan of the Venetian republic, doges (the name their presidents received) were elected for life. However, a long tenure was a rare event, which effectively resulted in term limits, as has already been reported by several authors. In this paper, we examine the length of these tenures and their evolution during the existence of the Venetian republic, following Smith et al.’s claim that specific events in Venetian history caused this shortening, but also the dates and possibly event or events that effectively caused that limitation by design. Finally, we will discuss the causes of this limitation and its effective consequences.